2010
DOI: 10.1590/s1807-59322010001000012
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional scanning with dual-source computed tomography in patients with acute skeletal trauma

Abstract: OBJECTIVE:The aim of this study was to compare the efficiency of multiplanar reformatted images and three‐dimensional images created after multidetector computed tomography examination in detecting acute post‐traumatic osseous pathology of the skeletal system.METHOD:Between October 2006 and December 2008, 105 patients with a history of acute trauma were referred to our service. Patients were evaluated with multidetector computed tomography using multiplanary reconstructed images initially (R‐I), and six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They emphasized that need for comprehensive studies with a larger sample size and studies designed to compare the results with a normal population to understand the clinical importance of their findings. Yildirim et al 105 compared the efficiency of multiplanar reformatted images and three dimensional images created after multidetector computed tomography examination in detecting acute post-traumatic osseous pathology of the skeletal system and found that dual source multidedector tomography systems trauma patients may be evaluated by multiplanary and three dimensionally reconstructed images. When used correctly, three dimensional imaging is advantageous and can help determine the exact nature and extension and also importance of osseous injuries.…”
Section: Animal Modelsmentioning
confidence: 99%
“…They emphasized that need for comprehensive studies with a larger sample size and studies designed to compare the results with a normal population to understand the clinical importance of their findings. Yildirim et al 105 compared the efficiency of multiplanar reformatted images and three dimensional images created after multidetector computed tomography examination in detecting acute post-traumatic osseous pathology of the skeletal system and found that dual source multidedector tomography systems trauma patients may be evaluated by multiplanary and three dimensionally reconstructed images. When used correctly, three dimensional imaging is advantageous and can help determine the exact nature and extension and also importance of osseous injuries.…”
Section: Animal Modelsmentioning
confidence: 99%